Of memory & furniture: poems in four parts and The flesh and the word: the modified female body - Bateman, Bronwyn Jane (Curtin University, 2011)
The poems in this collection are about the relationship between the female body and its experiences of being culturally silenced by childhood sexual abuse, mental illness and institutionalised maternity. They also articulate ways of writing resistance to that silencing through representing in poetry lesbian embodiment, volitional markings such as tattooing, cutting and piercing, and temporary marking and constraint of the body through consensual D/s [Dominance and submission].